The impact of the audit committee on the disclosure of intellectual capital: An applied study in Sudanese industrial companies - Abdullah, Sabi Mahmood; Elnour, Mohamed Elnair Mohamed (Journal of Economic, Administrative and Legal Sciences, 2024)
The purpose of the research is to examine the impact of the audit committee as one of the governance mechanisms and its effect on the level of disclosure of intellectual capital in Sudanese industrial companies. The study analyzes the annual reports of Sudanese industrial companies for the period from 2015 to 2021. Regression and correlation analysis were used to determine the relationship between the research variables. The study found a significant relationship and impact of the audit committee on the level of intellectual capital disclosure. The research recommends conducting further accounting research and studies related to the extent to which companies implement governance mechanisms and disclose intellectual capital.